Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13690-020-00482-3
|View full text |Cite
|
Sign up to set email alerts
|

Eating quickly is associated with a low aspartate aminotransferase to alanine aminotransferase ratio in middle-aged adults: a large-scale cross-sectional survey in Japan

Abstract: Background An elevated alanine aminotransferase (ALT) and a low aspartate aminotransferase (AST) to ALT ratio (AST/ALT ratio) suggest nonalcoholic fatty liver disease and nonalcoholic steatohepatitis, increasing the risk of liver cirrhosis and hepatocellular carcinoma. In addition, eating quickly has been found to be associated with outcomes such as obesity. This study sought to investigate the relationship between eating quickly and an elevated ALT or a low AST/ALT ratio in Japanese middle-aged adults. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, both studies con rmed an association of GOT1 with cancer progression and acquisition of castration resistance, and that its knockdown suppresses cancer progression. Another report noted that ALT, unlike AST, is produced exclusively in the liver and largely unaffected by other factors such as cancer, and may decrease with liver aging 32) . The present ndings that ALT was decreased and AST increased during long-term cancer treatment are consistent with those previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both studies con rmed an association of GOT1 with cancer progression and acquisition of castration resistance, and that its knockdown suppresses cancer progression. Another report noted that ALT, unlike AST, is produced exclusively in the liver and largely unaffected by other factors such as cancer, and may decrease with liver aging 32) . The present ndings that ALT was decreased and AST increased during long-term cancer treatment are consistent with those previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both studies confirmed an association of GOT1 with cancer progression and acquisition of castration resistance, and that its knockdown suppresses cancer progression. Another report noted that ALT, unlike AST, is produced exclusively in the liver and largely unaffected by other factors such as cancer, and may decrease with liver aging 32 . The present findings that ALT was decreased and AST increased during long-term cancer treatment are consistent with those previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…ALT is a more liver‐specific measurement than AST. 19 People who experience hepatic aging, indicated by low ALT levels, may produce more free radicals and oxidative stress, 12 causing cancer. In addition, a previous study reported lower ALT levels in the sera of patients with invasive cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothetical mechanism for the association is the pathophysiological mechanism. ALT is a more liver‐specific measurement than AST 19 . People who experience hepatic aging, indicated by low ALT levels, may produce more free radicals and oxidative stress, 12 causing cancer.…”
Section: Discussionmentioning
confidence: 99%